CLASS 10 Chapter 3 example 5 new maths textbook 2023

แชร์
ฝัง
  • เผยแพร่เมื่อ 8 ก.พ. 2025
  • Q1) Aftab tells his daughter, “Seven years ago, I was seven times as old as you were then. Also, three years from now, I shall be three times as old as you will be.” (Isn’t this interesting?) Represent this situation algebraically.
    must watch this video : • Age Problems
    -------------------------------------------------------------
    LIKE COMMENT SHARE SUBSCRIBE
    follow us on insta @kulsanketkumar
    -------------------------------------------------------------
    Chapter 1 Real Number------- bit.ly/3dyeOSe
    Chapter 2 Polynomial-------- bit.ly/3mhgLGI
    Chapter 3 Linear Equation---------
    Chapter 4 Quadratic Equation---------
    Chapter 5 Arithmetic
    Progression-----..​
    Chapter 6 Triangles-------
    Chapter 7 Co-ordinate Geometry-------
    Chapter 8 Trigonometry---------
    Chapter 9 Application Of Trigonometry-------
    Chapter 10 Circle-------
    Chapter 11
    Construction--------
    Chapter 12 Area Related to Circle--------
    Chapter 13 Surface Area and Volume-------
    Chapter 14 Statistics-------
    exercise 3.1 ka question 10
    class 10 new syllabus
    chapter 3 solved example
    solved example 5 chapter 3
    #10maths
    #basicmaths
    #standardmaths
    #cbsemaths
    #linearequation
    #pairoflinearequation
    #chapter3solutions
    #excercise3.1Q1
    #ex3.1q1
    NCERT Solutions for Class 10 Maths Chapter 3- Pair of Linear Equations in Two Variables
    Solutions:Let the present age of Aftab be ‘x’.
    And, the present age of his daughter be ‘y’.
    Now, we can write, seven years ago,
    Age of Aftab = x-7
    Age of his daughter = y-7
    According to the question,
    x−7 = 7(y−7)
    ⇒x−7 = 7y−49
    ⇒x−7y = −42 ………………………(i)
    Also, three years from now or after three years,
    Age of Aftab will become = x+3.
    Age of his daughter will become = y+3
    According to the situation given,
    x+3 = 3(y+3)
    ⇒x+3 = 3y+9
    ⇒x−3y = 6 …………..…………………(ii)
    Subtracting equation (i) from equation (ii) we have
    (x−3y)−(x−7y) = 6−(−42)
    ⇒−3y+7y = 6+42
    ⇒4y = 48
    ⇒y = 12
    The algebraic equation is represented by
    x−7y = −42
    x−3y = 6
    For, x−7y = −42 or x = −42+7y
    now make solution table and plot the graph

ความคิดเห็น • 33